Everolimus Related Fulminant Hepatitis in Pancreatic Neuroendocrine Tumor With Liver Metastases: A Case Report and Literature Review - Chang, Shih-Chun; Tsai, Chun-Yi; Liu, Keng-Hao; Wang, Shang-yu; Hsu, Jun-Te; Yeh, Ta-Sen; Yeh, Chun-Nan (Frontiers in Endocrinology, 2021)
Background Everolimus, an immunosuppressant, is approved for the treatment of advanced renal cell carcinoma, metastatic hormone receptor-positive breast cancer, and pancreatic neuroendocrine tumors (P-NETs) but has been reported to be related to hepatitis B reactivation. Here, we present the first case of fatal fulminant hepatitis B reactivation in a man with P-NET accompanied by multiple liver metastases who received everolimus and octreotide long-acting repeatable (LAR). Case Presentation A 45-year-old male had a history of chronic hepatitis B infection. He was found to have a complicated liver cyst incidentally, and then he underwent biopsy, which disclosed a grade 2 neuroendocrine tumor (NET). Subsequent MRI of the abdomen and PET revealed a solid mass at the pancreatic tail with numerous liver tumors favoring metastases and peripancreatic lymph node metastases. Transarterial chemoembolization (TACE) of the right lobe of the liver was performed, and he started to take 5 mg everolimus twice a day and 20 mg octreotide LAR every month 8 days after the 1st TACE. No hepatitis B virus (HBV) prophylaxis treatment was administered. He then underwent laparoscopic distal pancreatectomy and splenectomy three and half months after the initial treatment of everolimus. He continued everolimus 5 mg twice a day and octreotide 20 mg every month after the operation. Three months later, hepatic failure occurred due to acute hepatitis B flare-up–related fulminant hepatic failure since other possible causes of hepatic failure were excluded. Five days after hepatic failure presented, hepatic failure was apparent, and pulseless ventricular tachycardia occurred. The patient expired after failed resuscitation. Conclusion A literature review of everolimus-related hepatitis B reactivation was conducted. In P-NET patients with chronic hepatitis B who will undergo everolimus treatment, HBV prophylaxis should be considered since fatal hepatitis B reactivation might occur under rare conditions.